THU0682 Human histocompatibility antigens (HLA) class 1 in anterior uveitis patients with and without spondyloarthritis. (12th June 2018) - Godzenko, A.; Guseva, I.; Razumova, I.
Abstract : Background: Anterior uveitis (AU) and spondyloarthritis (SpA) are associated with HLA-B27. Previous genetic studies in different populations demonstrated other associations, in particular, HLA, both common and different for AU and SpA Objectives: To assess the relationship of HLA class I antigens with AU depending on the presence or absence of SpA Methods: 148 pts with AU were typed. All pts were divided into 2 groups: 1–52 pts with confirmed diagnosis of SpA (AU +SpA), 96 pts – with other forms of AU (52 – idiopathic AU, 29 – viral AU, 2- multiple sclerosis, , 2 - toxoplasmosis, 1- sarcoidosis, 1- tuberculosis, 3- chlamydial AU, 2 - Behcet's disease, 3 - juvenile chronic arthritis, 1 - Fuchs′s heterochromic iridocyclitis). 150 healthy donors formed control group. Analysis of the distribution of HLA- class I antigens (loci A, B, Cw) was performed comparing 2 groups of patients with AU and each group with control. Results: HLA-27 in the group of pts AU +SpA identified in 96.1% (50/52), in the group AU – in 40, 6% (39/96), in control – in 7.3% (11/150). If HLA-27 was present in the genotype, the risk of developing of common pathology (AU +SpA) was OR=315, 9 [95% CI 61, 9–2176, 7], p<0, 0000001, the risk of AU - OR=8, 7 [95% CI 3, 9–19, 4], p<0, 000001. Among locus C antigens high frequency of Cw2 was identified in the groups AU +SpA and AU compared with control (64, 0%, 36, 3% and 10.0%, respectively): AU +SpA vs control - p<0, 000001, AU vs control, - p<0 00 001. The occurrence of Cw7 was significantly lower in the group AU +SpA in comparison with control: 12.8% and 38.7%, p=0002. In the group AU the occurrence of this antigen was not significantly different from the control group and the group AU +SpA. Conclusions: The analysis of the distribution of HLA class I antigens confirmed association of HLA- B27 with AU in Russian population. Other associations, except Cw2, were not identified. Such significant increase of Cw2 in two groups of pts with high frequency of B27 is natural due to the phenomenon of linkage disequilibrium for HLA-B27 and Cw2 antigens. Cw7 antigen can play a "protective" role in relation to SpA, because the frequency of this gene in the group AU was not reduced compared to control. Reference: [1] Robinson PC, Claushuis TA, Cortes A, et al. Genetic dissection of acute anterior uveitis reveals similarities and differences in associations observed with ankylosing spondylitis. Arthritis Rheumatol.2015Jan;67(1):140–51. doi:10.1002/art.38873 Disclosure of Interest: None declared